Turning control of a mobile robot for greenhouse spraying based on dynamic sliding mode control. (12th December 2017) - Gao, Guoqin; Qin, Qiuyue; Chen, Sheng
The road of a greenhouse is both damp and narrow, and there are both ground obstacles and space obstacles in a greenhouse, which easily cause the instability problem for a four-wheel independent driving greenhouse spraying mobile robot turning in the greenhouse. In order to improve the steering performance of the greenhouse spraying mobile robot, based on the characteristics that each wheel torque of the robot can be separately controlled, the dynamic model of the four-wheel independent steering system is firstly established using D'Alembert's principle and choosing the sideslip angle and the yaw velocity as the state variables. Then, based on the theory of sliding mode control, a dynamic sliding mode control strategy with exponential approaching rate is proposed by adopting the sideslip angle and the yaw velocity as the joint control variables in order to make the sideslip angles be in the stable range and make the yaw velocity track the desired value well. Finally, the simulation of the steering performance is performed using MATLAB/Simulink. The control response curves of the yaw velocity and the sideslip angle of the robot's mass center in a step input and in a sinusoidal input are obtained, respectively. It is shown from the simulation results that compared with the feedforward–feedback control method, the proposed dynamic sliding mode control strategy based on the established dynamic model is effective to improve the turning control stability of the mobile robot for greenhouse spraying. The experiment results further verify the feasibility of the proposed turning control strategy.